Post breeding heifer management - Johnson, Sandra K.; Funston, Richard N. (My University, 2014)
Rebreeding performance of the first calf heifer has major economic consequences for cow-calf producers. Management systems that allow heifers to cost effectively achieve a body condition score of 5 to 6 at calving and maintain this through rebreeding have a higher probability of pregnancy success.
Keywords: Primiparous; Body Condition; Nutrition; Pregnancy; Ionophore; Postbreeding heifer management